Resilience and Suicide Idea of First Year Students of D-III Nursing Blitar - Balbly, Zahra Dewi Azhari; Ulum, Mochamad Miftahul; Anam, Agus Khoirul (Health Access Journal, 2024)
First-year nursing students are required to integrate material with skill laboratories and practice areas, which puts pressure on students who can lead to the emergence of suicidal ideation so that an ability called resilience is needed. The purpose of this study was to determine the relationship between the level of resilience and the level of suicidal ideation of first year students of D-III Kpeerawatan Blitar. The method used is correlation method with cross sectional design. The sample in this study were 101 D-III Nursing Blitar 1st year students who were taken using the total sampling technique. The instruments used were ARS and SSI questionnaires. The results showed that there was a relationship between the level of resilience and suicidal ideation with a p-value of 0.002. the higher the resilience, the lower the suicidal ideation and vice versa, the lower the resilience, the higher the suicidal ideation.